Coastal cooling and increased productivity in the main upwelling zone off Peru since the mid-twentieth century - Gutierrez, D (2011)
This study was supported by IMARPE(Peru), the research unit LOCEAN‐IPSL (UMR 7192 CNRS/IRD/UPMC/MNHN) in France and the projects JEAI MIXPALEO,PALEOPECES, PALEOTRACES, DISCOH, PCCC and the‘CátedraCONCYTEC en Ciencias del Mar’. We thank Jorge Vasquez (JPL) for pro-viding the 4km resolution GHRSST‐PP SST data and David Correa forperforming the objective interpolation of these data. Finally, we thankFrancisco Chavez and Monique Messié, with whom we sustained sounddiscussions that helped us for the preparation of this paper.